Tourism Development Strategies on CBT of Pindul Cave, Gunungkidul Regency - Syuhada, Muhammad Raditya Fajar; Dewanti, Diah Setyawati (Program Studi Ekonomi FEB UMY, 2020)
The purposes of this research are to determine the strengths, weaknesses, opportunities and threats of Pindul Cave Tourism Object as well as create the best strategies in efforts to developing Pindul Cave Tourism Object to increase community income. This research used a descriptive approach, by collecting data in the form of primary data. The analysis technique used in this research are observation, interviews, Focus Group Discussion and documentation. The subjects on this research are managers of tourism object such as Government Tourism Office, Secretary of District, POKDARWIS of Pindul Cave, and tourism stakeholders, seller of bakso tusuk, parking guards, guide. The analysis tool of this research is SWOT analysis. Based on SWOT analysis identifications of Pindul Cave Tourism Object development strategies the results of data collected are; 1) internal factors of Pindul Cave Tourism Object which are strengths and weaknesses that can support and inhibit the development of tourism object. 2) external factors of Pindul Cave Tourism Object which are strengths and weaknesses that can support and inhibit the development of tourism object. 3) the best strategy can be executed by PindulÂ Cave Tourism Object which is SO strategy (Strengths and Opportunities).